KETERBUKAAN INFORMASI PUBLIK : Perangkat Baru Menciptakan Good Governance dalam Pemerintahan Lokal - Saleh, Luluk (Jurnal Konstitusi, 2010)
In this local autonomy era, there is merely little information the people may access about the operation of the government through either electronic or printed media which are provided with by local governments. However, important information is still difficult to obtain, as a result, it is thought that  the operation of local governments is not fully transparent and is not yet good governance-based. One of important tools to realize good governance is a public information openness. The momentum of such an openness becomes real when the Parliament  legalized the 2008 Law no 14 on the  Public Information Openness on April 3, 2008. The law comprehensively regulates the  duties of the public officers/bodies in giving an access to information, documents and data  which are integrated as an inherent part of the function of government bureaucracy, reinforced by strict sanctions for those breaking them.